Morphological features eutopic endometrium in women with adenomyosis and chronic pelvic pain syndrome. - Dubossarskaya, Z. M.; Grek, L. P.; Skorik, V. R. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Chronic pelvic pain syndrome is one of the most frequent pathologies that reduce quality of woman`s life. The main reason for its occurrence is gynecological diseases (extragenital endometriosis, adenomyosis, uterine leiomyoma). But role of morphological changes in the endometrium for the occurrence of these diseases is still unexplored. Objective. Assess the links between morphological and immunohistochemical (markers ER, PGR, Ki-67, VEGF, COX-2, NF) features and the level of pain on VAS. Methods. 10 samples were divided according to expression of investigated marker in glands (ER, PGR, Ki-67, VEGF, COX-2, NF) and in stroma (ER, PGR, Ki-67). Rating staining immunohistochemical markers was conducted in at least 10 fields of view. Statistical processing of the data included nonparametric tests. Results. We observed heterogeneous expression of ER, PGR, more importat role of high level expression PRG in stroma, increased proliferative activity in glands is focal in the most cases. Expression of VEGF is often higher, when the level of VAS is up. Conclusion. Formation of the CPP and adenomyosis is associated with hyperplastic processes of endometrium , increased proliferative activity , and severe expression of COX - 2 ( p < 0.05 ).